A volcanic and gravity flow controlled fine-grained organic rich deposits of the lower Jurassic Beipiao formation in the Western Liaoning, northeast China - Wen, Jiucun; Xu, Jie; Jiang, Zaixing; Liu, Tong; Meng, Jiayi; Zhang, Jiazhi; Wei, Siyuan; Shen, Zhihan; Li, Yongfei; Zhang, Xi (Frontiers in Earth Science, 2024)
IntroductionThe Lower Jurassic Beipiao Formation in the western Liaoning of northeast China represents a significant case study for understanding the interplay between volcanic activity, sedimentary processes, and organic matter enrichment.MethodsThis study aims to investigate the lithofacies, depositional environments, and hydrocarbon potential of the Beipiao Formation, using core, outcrop, thin-section, and geochemical data.ResultsThirteen lithofacies types were identified, which reflect a complex depositional history influenced by volcanic processes and gravity flows. The sedimentary facies analysis revealed three key depositional environments: shallow lake, semi-deep to deep lacustrine, and fan delta. The basin evolution suggests a transition from fan delta deposits to deep lake deposits and then back to fan delta, with volcanic and gravity flow deposits interbedded. Volcanic activity not only provided nutrient-rich environments conducive to biological productivity but also helped create conditions favorable for organic matter preservation. The earthquake, flooding or stormed events induced gravity flow, which favored plant fragments dispersal to the deep-lake and formed type III kerogen in the deep-lake developed area.DiscussionThese findings suggest that the Jurassic Beipiao Formation in western Liaoning Province, exhibit significant hydrocarbon potential. This challenges previous assumptions regarding the dominance of shallow water environments and limited exploration prospects within the Yanshan Orogenic Belt. Furthermore, this study highlights the crucial role of volcanic activity and gravity flow in organic matter enrichment, transportation, and preservation within a volcanic-rift basin, with potential applicability to similar basins worldwide.